Toward high efficiency at high temperatures: Recent progress and prospects on InGaN-Based solar cells. (January 2023) - Zhao, Yuji; Xu, Mingfei; Huang, Xuanqi; Lebeau, Justin; Li, Tao; Wang, Dawei; Fu, Houqiang; Fu, Kai; Wang, Xinqiang; Lin, Jingyu; Jiang, Hongxing
Abstract: III-nitride InGaN material is an ideal candidate for the fabrication of high performance photovoltaic (PV) solar cells, especially for high-temperature applications. Over the past decade, significant efforts have been made to improve the PV performance of InGaN-based solar cells. In this paper, we perform a comprehensive review of the recent developments in InGaN-based solar cells. The topics of discussion include theoretical modeling, material epitaxy, device engineering, and high-temperature measurement. Particularly, we highlight subjects such as substrate technology, and properties that are unique to InGaN materials such as polarization control and their positive thermal coefficient. To date, outstanding high-temperature InGaN-based solar cells with quantum efficiency approaching 80% at 450 °C have been demonstrated. Future innovations in epitaxy science, device engineering, and integration methods are required to further advance the efficiency and expand the applications of InGaN-based solar cells. Graphical abstract: Image 1 Highlights: A detailed summary of theoretical modeling of InGaN solar cells. State-of the-art techniques for InGaN epitaxial growth. Effective device engineering methods to improve the performance of InGaN solar cells. High temperature performance of InGaN solar cells including temperature coefficient and carrier dynamics.